DETERMINATION OF ENERGY VALUES OF BEE PRODUCTS MIXED WITH HERBAL SOURCES AS A PERFORMANCE-ENHANCING ENERGY SOURCE FOR SPORTSMEN - ARTIK, Nevzat; KARAMAN, Mehmet Rüştü (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2019)
Athletes should consume a wide variety of foods that meet their energy needs and provide optimum amounts of carbohydrate, protein, fat, vitamins, minerals and other important food components. Especially, carbohydrates are the most essential nutrient in an athlete’s diet because they are the only fuel that can sustain intense exercise for extended durations. It is believed that bee products such as honey, propolis, royal jelly, bee pollen and bee bread are the best supplements for human nutrition and health, but there is limited information on the ergogenic effects of bee products on sports performance. The main target of this study was to analyse some energy components, minerals, vitamins etc. of bee products such as perga vital to determine their potential as a performance-enhancing energy sources for athletes. Perga vital is a raw honey, pure perga (bee bread), pollen, carob powder black grape seed powder mixture, especially developed as a natural food according to scientific norms in Technopark Region of Ankara University. For this aim, energy values (kcal/kJ per 100 g), protein (%), fat (%), carbohydrates (%), fiber (%), sucrose (%), glucose (%), fructose (%), glucose + fructose (%),moisture (%), water-insoluble matter (g 100g-1 ), Naphthalene, mg kg-1 HMF (mg kg-1 ), free acidity (meq kg-1 ), number of diestas, total phenolics (mg 100g-1 ) and antioxidant capacity (mg 100 g-1 ) of perga vital were analysed according to the routine methods. The findings have revealed that bee products have an abundance of vitamins, minerals, enzymes and phytonutrients, which are all important in achieving optimal health and performance of athletes. Furthermore, perga vital can be an effective carbohydrate source and a better substitute to glucose for exercise and athletic performance, due to its constituent of various classes of sugars. However, standardisation of quality properties of the bee products such as perga vital will be valuable for their optimal performance effects for sportsmen.